Recurso educativo y aprendizaje sobre Instrumentación básica dirigido a estudiantes de Medicina de la Universidad Nacional de Loja - Paladinez Vinces, Kevin Adrian (2024)
For Higher education institutions have the fundamental role of developing effective teaching methods, with educational resources being innovative tools that optimize learning through clinical simulation, which helps students develop skills that will be useful in various scenarios they may encounter in their professional lives. In this context, the present mixed prospective cross-sectional cohort study was conducted with the aim of implementing a simulation workshop based on basic surgical instrumentation aimed at medical students of the National University of Loja. A clinical practical guide that enhances student knowledge was developed, along with a video as an educational resource, which is easily accessible without limitations and was recorded in the faculty's Procedures laboratory. These resources meet the parameters and objectives of the subject. A simulation workshop was held, and prior to this, the developed educational resources were provided. The acquired knowledge was then evaluated through an Objective Structured Clinical Examination, where out of 38 students, in the first ECOE prior to the educational resources, they achieved grades in the ranges of 21.05% (n=8) received a "very good" rating, 52.63% (n=20) "good," 21.05% (n=8) "fair," and 5.26% (n=2) "insufficient." No results were reflected for outstanding, after the educational resources were provided, the second ECOE shows the following results in the range from outstanding (16 points) to good (8 points), with the following outcomes: 71.05% (n=27) achieved an "outstanding" grade, 26.31% (n=10) "very good," and 2.63% (n=2) "good," with 100% of them passing after the workshop. This concludes that the planning, execution, and dissemination of educational resources, as well as the implementation of the clinical simulation workshop, developed and enriched the knowledge of the participating students on surgical instrumentation, representing an innovative and effective medical training through clinical simulation